Eksplorasi Pendidikan Kesehatan Ibu tentang Stimulasi Perkembangan Anak pada Masyarakat Nelayan Kabupaten Bone - Nirmawati Darwis; Ruslang Ruslang; Yammar Yammar; Anugerah Yanuar Azis; Haswinda Puspita (Journal Research of Nursing & Midwifery (JRNM), 2025)
Early childhood development stimulation has a significant impact on their cognitive, motor, and social growth. The knowledge and practices of mothers in providing developmental stimulation are crucial, especially in communities facing social and economic challenges, such as fishing communities. This study aims to explore the knowledge, practices, challenges, and sources of information related to child development stimulation among mothers in Bone Regency. This study uses a qualitative approach with in-depth interviews. A total of 15 mothers with children aged 0-24 months were selected using purposive sampling. The collected data were analyzed using the Colaizzi method to identify key themes. The majority of mothers have basic knowledge about motor and language stimulation, but they lack understanding of social and cognitive stimulation. The stimulation practices they carry out focus on gross motor stimulation and language through daily conversations. The main challenges faced are limited time due to work as fishermen and economic constraints that affect access to information. The primary sources of information come from personal experience, family, and close friends, with few accessing health services or mass media.The results of the study emphasize the importance of enhancing maternal health education on social and cognitive child stimulation. Additionally, better access to information through effective channels is needed, especially for mothers in areas with time and economic constraints. Community-based education and outreach can improve mothers' understanding and practices in child development stimulation.